Analisis Kemampuan Pemecahan Masalah Siswa Kelas IV SD pada Soal HOTS FPB dan KPK Berdasarkan Teori John Dewey - Mukhammad Fauzan Kurniawan; Dinda Dwi Piskawati; Riana Nanda Priyani; Puput Gadis Widiana; Putri Ngamilul Maqfiroh; Rissa Prima Kurniawati (Prosiding Konferensi Ilmiah Dasar, 2026)
This study aims to describe the mathematical problem-solving abilities of fourth-grade elementary school students in solving Higher Order Thinking Skills (HOTS) problems on the Greatest Common Factor (GCF) and Least Common Multiple (LCM) based on John Dewey’s problem-solving theory. This research employed a descriptive qualitative approach involving five fourth-grade elementary school students selected through criterion sampling. Data were collected through essay tests and documentation, while data analysis was conducted using the Miles, Huberman, and Saldana model, consisting of data reduction, data display, and conclusion drawing. The results showed that students’ mathematical problem-solving abilities were generally categorized as good. Four subjects were able to complete all stages of John Dewey’s problem-solving process, including identifying problems, defining problems, developing solutions, testing solutions, and drawing conclusions. Meanwhile, one subject experienced difficulties in the solution-testing stage because not all available information in the problem was utilized. These findings indicate that John Dewey’s problem-solving stages can systematically describe students’ mathematical thinking processes and can be used as a reference for improving mathematical problem-solving abilities in elementary school learning.